Allelopathic effect of waste-land weeds on germination and growth of winter crops - Hayyat,Muhammad S. (2020)
Abstract Background: Waste-land weeds present around the fields exert their allelopathic influence on crops through their leaf leachates and rhizospheric soils. Objective: A study was conducted to investigate the phytotoxic action of four common waste-land weeds Parthenium hysterophorus L., Achyranthes aspera L., Lantana camara L. and Withania somnifera L. through their aqueous extracts and rhizospheric soils against winter crops Avena sativa L., Cicer arietinum L., Hordeum vulgare L. and Triticum aestivum L. Methods: Experiments were conducted in Agronomy laboratory in College of Agriculture at the University of Sargodha. In first experiment, 5% (w/v) water extract from entire plant of each weed was applied to germinating seeds of crops whereas in second experiment, crop seeds were subjected to the rhizospheric soil of each weed for germination test. Results: Results revealed that aqueous extracts of weeds were more phyto-inhibitory compared to their rhizospheric soils. Minimum germination percentage (42.5%), germination index (7.4), seedling vigor index (665.3), root length (3.27 cm), seedling length (14.15 cm) and seedling biomass (74.2 mg) of crops were recorded in response to aqueous extract of P. hysterophorus. Root growth of the crops was affected more compared to the shoot growth. Minimum germination percentage was observed in A. sativa (13.3) by the action of L. camara aqueous extract. Rhizospheric soil of L. camara and P. hysterophorus resulted in minimum germination percentages (57.5 and 58.3, respectively) and seedling vigor indices (1472.5 and 2008.4, respectively) of crops. The lowest germination (30%) and germination index (3.7) was observed for T. aestivum seeds germinated in the rhizospheric soil of W. somnifera. Among crops, A. sativa and C. arietinum were more susceptible to the aqueous extracts whereas T. aestivum to rhizospheric soils of weeds. Conclusions: It can be concluded that waste-land weeds especially P. hysterophorus and L. camara negatively affect the crops by their allelopathy.